Improving the Digital-Based Financial Management Capacity of MSMEs to Enhance Community Economic Competitiveness - Luther Hasan Lase1; Ristanto; Bambang Mardi Sentosa (LPPM Akademi Teknik Adikarya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in boosting economic growth, but they still face various challenges in financial management, particularly related to transaction recording, financial planning, and the use of digital technology. This community service program aims to improve the digital-based financial management capacity of MSMEs to strengthen their economic competitiveness. The program implementation method includes identifying partner needs, simple financial management training, mentoring in the use of digital financial recording applications, and evaluating the implementation of business financial management systems. Participants were MSMEs in the target area who have limitations in implementing technology-based financial management. The results of the program showed an increase in participants' understanding and skills in systematic financial recording, separating business and personal finances, and preparing simple financial reports using digital applications. In addition, business owners began to be able to utilize financial data for business planning and economic decision-making. This program also resulted in increased business management efficiency and opened up market expansion opportunities through integration with digital platforms. Therefore, strengthening digital-based financial management capacity is a crucial strategy in supporting business sustainability and increasing community economic competitiveness. This program is recommended to be continued through ongoing mentoring to ensure the consistent implementation of digital financial management in MSMEs